The Role of Self Control in Mediating the Influence of Social Media Advertising Exposure and Digital Financial Literacy on the Consumptive Behavior of Grade XI High School Students in South Kotabumi District, North Lampung Regency - Latifah Asmul Faoziah; Maimun Sholeh (International Journal of Economics, Management and Accounting, 2026)
This study aims to analyze the effect of social media advertising exposure and digital financial literacy on consumptive behavior, with self-control as a mediating variable among 11th grade high school students in Kotabumi Selatan District. This quantitative study involved 267 respondents from five public and private high schools selected using proportional sampling techniques. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that exposure to social media advertising has a significant positive effect on consumptive behavior, indicating that higher advertising exposure increases students’ tendency toward excessive consumption. However, advertising exposure does not have a significant effect on self-control. Digital financial literacy has a significant positive effect on self-control, but does not directly influence consumptive behavior. Furthermore, self-control has a significant negative effect on consumptive behavior and plays a mediating role in the relationship between digital financial literacy and consumptive behavior. These findings confirm that strengthening digital financial literacy is crucial for improving adolescents’ self-control and reducing consumptive behavior in the digital era.